Apparent digestibility of broken rice in horses using in vivo and in vitro methods. (21st November 2013) - De Marco, M.; Peiretti, P. G.; Miraglia, N.; Bergero, D.
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of this study was to assess the apparent digestibility of broken rice using total collection of feces and the pepsin-cellulase in vitro technique to provide updated and more accurate digestion coefficients for this by-product when fed to horses. The in vivo digestibility trial was consecutively performed, using five adult geldings, weighing 555.6 kg on average. First, hay was given as the only feedstuff, while second, the experimental diet consisted of the same hay plus broken rice at a forage-to-concentrate ratio of 70/30 (on dry matter (DM) basis). Feces were collected over 6 days preceded by a 14-day adaptation period. The digestibility trial was carried out to determine the digestion coefficients for DM, organic matter (OM), CP and gross energy in both diets, while apparent digestion coefficients for the same parameters were calculated for broken rice alone, using the difference between the two sets of results. At the same time, an in vitro trial was carried out using pepsin-cellulase technique on the samples of hay and broken rice tested during the in vivo trial. As expected, supplementation with broken rice increased digestibility according to all the parameters used. The high OM digestion coefficients of broken rice were confirmed both by the calculated in vivo method and by the predicted results of pepsin-cellulase technique (92.6% and 87.1%, respectively), underlining the high digestibility of this by-product when fed to horses.